Recursive Surveillance and the Persistence of Authoritarian Surveillance in Brazil - Melgaço, Lucas (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
To comprehend contemporary surveillance in Brazil, especially under Bolsonaro’s administration (2019–2022), it is crucial to revisit the country’s most authoritarian period, the military dictatorship (1964–1985). During this period, the National Information Service (SNI) was established as a state intelligence agency and played a pivotal role in monitoring and suppressing dissent, setting the stage for future surveillance practices in Brazil. The military dictatorship ended in 1985, with the SNI being dissolved in 1990. In 1999, the remnants of SNI were restructured into the Brazilian Intelligence Agency (ABIN), which remains operational today. Under Bolsonaro’s government, ABIN employed advanced surveillance technologies to monitor opponents of the far-right president. Some of these surveillance practices have been deemed abusive and are currently under investigation by the Federal Police during Lula’s administration (2023–2026). This contribution introduces the concept of recursive surveillance, suggesting that state surveillance mechanisms not only reinvent themselves but also do so in ways that create the framework for their examination and eventual exposure. Surveillance structures, particularly those created in authoritarian regimes, leave traces that may reveal the practices and ideologies of the watchers, allowing for their eventual scrutiny.